2,5-Disubstituted-4-Thiazolidinones: Synthesis, Anti-Inflammatory, Free Radical Scavenging Potentials and Structural Insights through Molecular Docking - Singh, Jagseer; Chawla, Pooja A.; Bhatia, Rohit; Singh, Shamsher (Letters in Organic Chemistry, 2021)
The present work reports the synthesis and screening of fifteen 2,5-disubstituted-4- thiazolidinones with different substitutions at imino and varied arylidene groups. The structures of the compounds were confirmed by spectral characterization. The compounds were subjected to in vivo anti- inflammatory and in vitro antioxidant activities. The derivatives possessed remarkable activities quite close to standard drugs used. Unlike conventional non-selective NSAIDs, the synthesized compounds did not contain any acidic group thereby ensuring possible freedom from ulcers. To further substantiate the claim for safer derivatives, the active compounds were docked against cyclooxygenase (COX)-2 enzyme. It was found that 4-fluorophenylimino substituent at 2- position and 3-nitro moiety on 5-benzylidene nucleus of the 4-thiazolidinone derivative fitted in the COX-2 binding pocket. The compounds exhibited remarkable activity in scavenging free radicals as depicted by DPPH assay method. The structure-activity relationship was also established in the present work with respect to the nature and position of the substituents. The active compounds were evaluated for drug-like nature under Lipinski’s rule of five and the toxicity behavior of active compounds was predicted using ADMETlab software. The compounds have the potential to target degenerative disorders associated with inflammation and the generation of free radicals.
Keywords: Knoevenagel condensation